Microscopic colitis demonstrates a T helper cell type 1 mucosal cytokine profile. Issue 4 (14th June 2006) - Tagkalidis, Peter P; Gibson, Peter R; Bhathal, Prithi S
Abstract : Background: Microscopic colitis (MC) is an inflammatory disorder of unknown aetiology. Aim: To characterise the mucosal cytokine profile of MC, with a view to understanding its potential pathogenic mechanisms. Methods: Cytokine profiles of mucosal biopse specimens taken at flexible sigmoidoscopy from 18 patients (8 with lymphocytic colitis and 10 with collagenous colitis) were analysed using real-time reverse transcriptase-PCR, in comparison with those from 13 aged-matched controls with diarrhoea-predominant irritable bowel syndrome. Biopsy specimens from six patients with histologically documented remission were available for comparative analysis. Biopsy specimens were also taken to determine the cellular expression of cytokine and cytokine-related proteins using immunohistochemistry. Results: Mucosal mRNA levels were 100 times greater for interferon (IFN)γ and interleukin (IL) 15, 60 times greater for tumour necrosis factor α, and 35 times greater for inducible nitric oxide synthase in MC compared with controls. Apart from a trend for increased levels of IL10, levels of other T helper cell type 2 (TH 2) cytokines including IL2 and IL4 were too low to be accurately quantified. Mucosal IFNγ mRNA levels correlated with the degree of diarrhoea, and returned to normal in remission. The immunohistochemical expression of cell junction proteins E-cadherin and ZO-1 was reduced in active disease. No differences were noted between lymphocytic and collagenous colitis for any of the above parameters. Conclusions: MC demonstrates a TH 1 mucosal cytokine profile with IFNγ as the predominantly upregulated cytokine, with concurrent induction of nitric oxide synthase and down regulation of IFNγ-related cell junction proteins. This pattern is similar to that in coeliac disease and suggests that it might represent a response to a luminal antigen.